National Education Policy 2020 and MPH programs-translating policy to practice - Angolkar, Mubashir; Dhagavkar, Pooja S.; Nagmoti, Jyoti; Zodpey, Sanjay (Frontiers in Education, 2025)
BackgroundPublic health education in India faces several challenges like non-uniform curricula, limited emphasis on experiential and competency-based learning, and inadequate infrastructure. Addressing these challenges demands significant changes in public health education to align it with Sustainable Development Goals 4 and National Education Policy (NEP) 2020 in particular. To overhaul the Masters of Public Health (MPH) program with a focus on holistic and multidisciplinary approaches, objective of this paper was to propose a framework for MPH program in alignment with NEP 2020.MethodsA thorough desk review of NEP 2020 for reforms in higher education was conducted. Nine documents by University Grants Commission (UGC) detailing implementation of the policy at higher education level were reviewed for their relevance to MPH programs. Various guidelines to align MPH programs with policy’s proposed reforms were identified. MPH framework was developed on the basis of these guidelines.ResultsMPH programs in India are not in alignment with NEP 2020 reforms. The framework suggested in this study includes guidelines on: (1) Flexible career pathways, (2) multiple entry and multiple exits, (3) levels, level descriptors, qualification specifications and graduate attributes, (4) credit system and Academic Bank of Credit, (5) evaluation and assessment, (6) Incorporation of Massive Open Online Courses (MOOC), Indian Knowledge System (IKS) Courses and Courses on Human Values and Ethics, and (7) provisions for recognition of prior learning (RPL) thus aligning the MPH program with selected policy reforms.ConclusionMPH programs can be aligned with certain reforms suggested by NEP 2020. The proposed framework can provide a solid background for transforming MPH programs in India, making them more flexible, interdisciplinary, research oriented and improving their quality.